An Efficient Protocol for Deriving Liver Stem Cells from Neonatal Mice: Validating Its Differentiation Potential - Sugapriya Dhanasekaran; Devilakshmi Sithambaram; Kavitha Govarthanan; Bijesh Kumar Biswal; Rama S. Verma (Analytical Cellular Pathology)
The success of liver regeneration depends on the availability of suitable cell types and their potential to differentiate into functional hepatocytes. To identify the stem cells which have the ability to differentiate into hepatocytes, we used neonatal liver as source. However, the current protocol for isolating stem cells from liver involves enzymes like collagenase, hyaluronidase exposed for longer duration which limits the success. This results in the keen interest to develop an easy single step enzyme digestion protocol for isolating stem cells from liver for tissue engineering approaches. Thus, the unlimited availability of cell type favors setting up the functional recovery of the damaged liver, ensuring ahead success towards treating liver diseases. We attempted to isolate liver stem derived cells (LDSCs) from mouse neonatal liver using single step minimal exposure to enzyme followed by in vitro culturing. The cells isolated were characterized for stem cell markers and subjected to lineage differentiation. Further, LDSCs were induced to hepatocyte differentiation and validated with hepatocyte markers. Finally, we developed a reproducible, efficient protocol for isolation of LDSCs with functional hepatocytes differentiation potential, which further can be used as in vitro model system for assessing drug toxicity assays in various preclinical trials.